Analisis Pengalaman Pembelajaran Jarak Jauh Secara Online pada Siswa SMA (Studi Kasus SMA Negeri 4 Malang) - Hening Endawila Noviani; Diah Priharsari; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Covid-19 pandemic is a health crisis that is currently occurring in all countries, including Indonesia. The application of Social Distancing affects all activities in aspects of life, one of which is in the field of education. Until now, the application of online distance learning methods is considered the right solution for learning activities during the Covid-19 pandemic. The application of online Distance Learning (PJJ) certainly provides new experiences for students. The purpose of this study aims to analyze the experiences felt by students during the online Distance Learning Process (PJJ) for high school students, especially SMA Negeri 4 Malang majoring in Mathematics and Natural Sciences (MIPA). The method used to perform the analysis is thematic coding analysis technique with data collection methods, namely interviews conducted online by telephone. The results of this study indicate that the application of Distance Learning (PJJ) online provides a pleasant experience for students, namely distance learning has time flexibility in its implementation. The results of the study found that experiences that were felt to be unpleasant for students were lack of understanding of the subject matter, lack of recognition of teacher characteristics as well as obstacles faced related to accessibility, environment, and technology.